Identification of Dominant Factor for Air Pollution Fluctuations at The Beginning of Covid-19 Large-Scale Social Restrictions (PSBB) in Jakarta - Sagita, Novvria; Saputra, Agung Hari; Novianti, Rima (Universitas Islam Lamongan, 2022)
A Coronavirus Diseases 2019 (COVID-19) stroke many countries at the beginning of 2020. It had an impact not only in the health field but also on the environment. Some countries enforced to lockdown policy. This condition impacted to increase the air quality in big cities in the world. However, the Indonesian government ruled large scale social restriction (PSBB) since April 2020. PSBB is not as strict as lockdown in other countries because society could go out for some crucial reason such as working, and getting food. Many researchers reported that the lockdown policy decreased air pollution in some big cities such as Beijing, Italy, etc. Therefore, this study aimed to identify the dominant factor of air pollution fluctuation 1-month before PSBB, during PSBB and 1-month after PSBB. Is only PSBB reducing social mobility caused changes of air pollutions such as CO, SO2, NO2, PM, and O3 or did meteorological factors such as relative humidity and wind speed also impact air pollutions concentration? To calculate the dominant factor by highest contribution value, this study used multiplication between the slope of pollutant to relative humidity or wind speed or social mobility and the slope of relative humidity or wind speed or social mobility to the time. The result showed that the social mobility at 1-month before PSBB, during PSBB and 1-month after PSBB was the dominant factor of CO decreasing at the rate of -0.44, -0.01, and -0.11 ppm. However, the contribution of relative humidity, wind speed and social mobility to other air pollutions did not always same as the trend of air pollutions.